2005
DOI: 10.1007/s00402-005-0796-4
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of substance-P nerves inside the infrapatellar fat pad and the adjacent synovial tissue: a neurohistological approach to anterior knee pain syndrome

Abstract: The occurrence and distribution of SP nerves inside the infrapatellar fat pad suggest a nociceptive function and a neurohistological role in anterior knee pain syndrome. The data support the hypothesis that a neurogenous infection of the infrapatellar fat pad could contribute to anterior knee pain syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 35 publications
3
82
0
Order By: Relevance
“…Experimental pain is acute and transient and does not necessarily reproduce knee OA pain, but for obvious reasons it is not possible to induce chronic pain experimentally. Nevertheless, the infrapatellar fat pad has nociceptive innervation (36), and is a source of pain in knee OA (37). The healthy subjects were significantly younger than the knee OA patients, and the patients were obese (BMI Ͼ30) in contrast to the healthy volunteers, but there are no relationships between either age or BMI and the peak knee moments used in the present study (44,45).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Experimental pain is acute and transient and does not necessarily reproduce knee OA pain, but for obvious reasons it is not possible to induce chronic pain experimentally. Nevertheless, the infrapatellar fat pad has nociceptive innervation (36), and is a source of pain in knee OA (37). The healthy subjects were significantly younger than the knee OA patients, and the patients were obese (BMI Ͼ30) in contrast to the healthy volunteers, but there are no relationships between either age or BMI and the peak knee moments used in the present study (44,45).…”
Section: Discussionmentioning
confidence: 71%
“…Recently, experimental pain was induced in the infrapatellar fat pad as a model of anterior knee pain leading to changes in quadriceps muscle coordination (34,35). The infrapatellar fat pad has nociceptive innervation (36) and is a source of pain in knee OA (37). The structure is intraarticular yet extrasynovial, reducing the risk of intrasynovial infection upon injections.…”
Section: Introductionmentioning
confidence: 99%
“…It is already known that inflammation leads to angiogenesis and sensory nerve growth along new blood vessels in osteoarthritic joints [13]. In the immunohistochemical analysis, neovessels and accompanying nerve growth have been reported in synovium [14] and fat pads [15,16] of osteoarthritic joints. However, to our knowledge, nobody has clearly demonstrated that these sensory nerves along vessels play an important role in patients' symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Subsynovial tissue and/or vascular synovium of bursae may contribute to nociception in a manner analogous to the synovial lining of the tibofemoral joint [17]; this nociceptive role could explain why bursectomy is sometimes helpful in refractory GTPS [18]. Furthermore, research examining the vascular and adipose subsynovial tissue may increase our understanding of the relationship between bursa and closely adjacent tendon pathology.…”
mentioning
confidence: 99%